Intelligent tracking control for robot manipulator including actuator dynamics via TSK-type fuzzy neural network. - Rong-Jong Wai
In this paper, a Takagi-Sugeno-Kang-type fuzzy-neural-network control (T-FNNC) scheme is constructed for an n-link robot manipulator to achieve high-precision position tracking. According to the concepts of mechanical geometry and motion dynamics, the dynamic model of an n-link robot manipulator including actuator dynamics is introduced initially. However, it is difficult to design a suitable model-based control scheme due to the uncertainties in practical applications, such as friction forces, external disturbances and parameter variations. In order to cope with this problem, a T-FNNC system without the requirement of prior system information and auxiliary control design is investigated to the joint position control of an n-link robot manipulator for periodic motion. In this model-free control scheme, a five-layer fuzzy-neural-network is utilized for the major control role, and the adaptive tuning laws of network parameters are established in the sense of projection algorithm and Lyapunov stability theorem to ensure the network convergence as well as stable control performance. In addition, experimental results of a two-link robot manipulator actuated by dc servomotors are provided to verify the effectiveness and robustness of the proposed T-FNNC methodology.
Keywords: Lyapunov stability theorem; Takagi-Sugeno-Kang type fuzzy control; Actuator dynamics; Adaptive tuning algorithm; Dc servomotor; Fuzzy neural network control; Intelligent tracking control; Mechanical geometry; Motion dynamics; Position tracking; Robot manipulator